ANALISIS PENGARUH PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. PERTAMINA PERSERO TERHADAP PENINGKATAN PENDAPATAN DAN PEMBERDAYAAN MASYARAKAT DESA KALIDONAN KABUPATEN CILACAP - Faris Multi Naufal,; Lorentino Togar Laut; Gentur Jalunggono (Universitas Tidar, 2019)
This research is intended to study the influence given by the Corporate Social Responsibility (CSR) program of PT. Pertamina in increasing people's income and economic empowerment of the community in Kalidonan Village, Cilacap Tengah District, Cilacap Regency. The study uses an analytical tool with different mean differences. With the method of collecting data through observation, interviews, documentation and literature. While the method of evaluating data uses deducative, inductive, and descriptive analysis methods. The results of the study were an increase in income earned by people who worked as farmers, farm laborers, fishermen and people who did not have permanent jobs. However, for community empowerment it still has not had a significant effect due to some contradictions caused by the Corporate Social Responsibility (CSR) Program of PT. Pertamina (PERSERO).Keywords: corporate social responsibility (CSR), increased income, communityempowerment